Aspek Pelindungan Hukum Atas Data Pribadi Nasabah pada Penyelenggaraan Layanan Mobile Banking pada PT. Bank Rakyat Indonesia Cabang Stabat - Riza Diandra Tanjung; Nurhilmiyah Nurhilmiyah (Dinasti Review Publisher, 2024)
The development of information technology, especially in the banking sector, customers can now easily access their financial services through mobile banking platforms. However, amidst such convenience, there are concerns about the security of customer data. The focus of this research is on written law or law on the books and customs, as the protection of personal data is crucial as the data stored in the banking system includes financial details, personal identity, and other sensitive data. This research uses normative legal research methods, which are also known by other terms such as positive legal research methods, doctrinal legal research methods, and pure legal research methods. The main regulations in Indonesia in this case are Law Number 19 of 2016 concerning Electronic Information and Transactions (UU ITE), as well as Bank Indonesia Regulations (PBI) regarding Information Security and Banking Transactions (PBI 18/40/PBI/2016). Protecting the personal data of BRI mobile banking customers requires a deep understanding of the various types of digital crime, including social engineering practices. With appropriate protection measures and high awareness from all relevant parties, it is expected to effectively reduce the risk of data leakage and maintain the security of clients' personal data.